Verbale klask, klagen og klynk: Retoriske strategier mellem hardcore og ‘klynke-rap’ - Krogh, Mads; Stougaard Pedersen, Birgitte (Danish Yearbook of Musicology, 2011)
The article investigates the work of a row of Danish rap artists, i.e. Liam O’Connor (alias L.O.C.) and Suspekt (Rune Rask, Emil Simonsen aka Orgi-E, and Andreas Duelund aka Bai-D). These artists have taken up dominant positions within the Danish rap scene and popular music culture throughout the recent decade. In 2009, however, they released a joint project entitled Selvmord (Suicide), whereby they surprisingly shifted their artistic expression from hardcore rap (inspired by American gangsta and horrorcore) to so-called ‘whimper’-rap – a term, coined by the Danish hip hop journalist, Ditte Giese. It is the rhetorical strategies concerning this shift, which is at stake in this article. We follow the artists’ path from celebrations of sex, drugs, and violence towards a growing selfreflexivity and vulnerability in their artistic expression. This development is investigated in the light of a duality between sincere, personal self exposure, on one side, and persona or alias on the other. This duality seems at work throughout the entire oeuvre of the rappers as ever present rhetorical strategies whose balance is, however, dislocated. Central to this dislocation is an interplay of authenticity and pathos framed within the rhetorical concept of signifyin(g) derived from discourses related to Afro-American storytelling (Gates).